Improving Student Activity in Grade 4 of Elementary School Combination Online Methods - Salsabila, Adina Alya; Rabbani, Queen Tauhida; Lestari, Rizki; Mahendra, Azizah Dwi; Adkhola, Najma Tsaqiba (Jurnal Inovasi Pembelajaran Karakter, 2024)
This study was conducted to improve student activeness in learning. Problems arose after sharing and surveying with parents, it was found that all students were bored at home with distance learning. The learning method to increase student activity is with distance learning combination. Combined distance learning is a combination of online (within the network) and offline (outside the network). This learning method is taken because learning is more varied. Students after getting the material in online form can then make observations/experiments/work on projects in the home environment. Students are not glued to the screen and module books, but students become more excited about activities with family around the house. This research is a classroom action research with the research subjects of 3rd grade students of SD IT Khoiru Ummah as many as 33 people. The research was carried out with 2 cycles, each cycle 2 meetings. Each meeting consists of 4 stages, namely planning, implementation, observation and reflection. The implementation of the research stages adjusts to distance learning which is carried out separately because students are in their respective homes. Based on the research results, in cycle I, an average of 74.5% of 33 students were active, while cycle II obtained an average of 92.5%. As a result, the combined distance learning method can increase student activity during the prevention of covid-19 Thematic subject Theme 1 Growth and Development of Living Things in grade 3 of SD IT Khoiru Ummah as much as 18%.